ChemInform Abstract: Gold(I)‐Catalyzed Dearomative [2 + 2]‐Cycloaddition of Indoles with Activated Allenes: A Combined Experimental—Computational Study. Issue 17 (April 2016) - Ocello, Riccardo; De Nisi, Assunta; Jia, Minqiang; Yang, Qing‐Qing; Monari, Magda; Giacinto, Pietro; Bottoni, Andrea; Miscione, Gian Pietro; Bandini, Marco
Abstract: The scope of the reaction encompasses both allenamides and aryloxyallenes as electrophilic partners.